Anti-AIDS Agents 73: Structure-Activity Relationship Study and Asymmetric Synthesis of 3-O-Monomethylsuccinyl Betulinic Acid Derivatives - Qian, Keduo (2007)
3-O-3′(or 2′)-methylsuccinyl-betulinic acid (MSB) derivatives were separated by using recycle HPLC. The structures of four isomers were assigned by NMR and asymmetric synthesis. 3-O-3′S-Methylsuccinyl-betulinic acid (3′S-MSB, 4) exhibited potent anti-HIV activity with an EC(50) value of 0.0087 μM and a TI value of 6.3×10(3), which is comparable to the data for bevirimat (DSB, PA-457), a current clinical trials drug that was also derived from betulinic acid. The anti-HIV potency of 4 was slightly better than that of AZT.